The Development of Computer Network Learning Media to Support Online Learning - Adi, Novi Hendri; Dewi, Indah Kusuma; Lubis, Arina Luthfini; Ambiyar, Ambiyar; Aminuddin, Fattachul Huda (Universitas Pahlawan Tuanku Tambusai, 2022)
In the new normal era, the learning system is carried out online. The lack of innovation in the use of learning media during the covid-19 pandemic, resulted in students being less motivated and having low learning enthusiasm in the computer network learning process. To overcome these problems, one alternative is to develop learning media during the pandemic. This research intends to improve computer network learning media as a support for online learning in the new normal era. The method used in this development research is Research and Development (R&D) using the Instractional Development Institute (IDI) model approach. The IDI approach model has several stages of implementation including define, develop, and evaluate. The results of the research on the development of learning media are declared valid, practical and effective to be applied as a computer network learning media as a media to support online learning.